HUBUNGAN ANTARA PERSIAPAN MENGAJAR GURU DENGAN DAYA TANGKAP SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN KELAS XI DAN XII DI SEKOLAH SMA 4 PSKD PANGLIMA POLIM - Tuti Waty Boang Manalu; Christina Metallica Samosir; Ronny Gunawan (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2019)
This study aims to find out how preparations for teaching the teacher with the catching power of class XI and XII students in SMA 4 PSKD Panglima Polim. In this study the population is students of class XI and XII SMA 4 PSKD Panglima Polim totaling 60 people. The method used in this research is quantitative descriptive method. The data obtained were analyzed using a percentage frequency distribution. The instrument used is a questionnaire with table form. This method is chosen because it suits the research objectives to be achieved. From the results of the research of the two variables shows that there is a positive and significant relationship between the preparation variables of teaching the teacher with the student's catching power. In other words, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, this is indicated by the correlation coefficient of 0.501 or 50.1% which shows the correlation of the two variables is positive. As well as the coefficient of determination of 0.251 or 25.1% which shows the teacher's teaching preparation variable has a relationship with the student's catching power of 25.1% while 74.9% is influenced by other factors. Another thing is also indicated by the ANOVA or F test, Fcount of 9.336 with sig. = 0.005